Preliminary Assessment Of Surface Water Quality Of Tropical Pilgrimage Wetland Of Central Gujarat, India - Soni, Hiren B; Thomas, Sheju (International Journal of Environment, 2013)
The present paper highlights the preliminary investigation of physico-chemical characteristics of tropical pilgrimage wetland viz. Dakor Sacred Wetland (DSW), Anand District, Central Gujarat, India. As the existing water body is contaminated with domestic sewage influenced by anthropogenic interventions, an urgent need was felt to evaluate physico-chemical parameters such as Temperature, pH, Dissolved Oxygen (DO), Total Solids (TS), Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Free CO2, Phenolphthalein Alkalinity (PA), Total Alkalinity (TA), Carbonates, Bicarbonates, Total Hardness, Calcium Hardness, Magnesium Hardness, Chloride, Salinity, Sulphate, Phosphate, Nitrate, Sodium, and Potassium. The obtained data were correlated statistically to draw a conclusion about the surface water quality of tropical pilgrimage wetland. Moreover, the results manifested the need and prime necessity to restore the physical, chemical and biological integrity with viable and rigorous restoration and management strategies in order to maintain, preserve, conserve and to avert the ecological imbalance and disturbance in hydro-geo-chemical and hydro-biological cycles, which adversely affect the food chain and food web of the significant pond ecosystem. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 202-223 DOI: http://dx.doi.org/10.3126/ije.v2i1.9222